Functional Characterization of a Novel R2R3-MYB Transcription Factor Modulating the Flavonoid Biosynthetic Pathway from Epimedium sagittatum - Huang, Wenjun; Lv, Haiyan; Wang, Ying (Frontiers in Plant Science, 2017)
Epimedium species have been widely used both as traditional Chinese medicinal plants and ornamental perennials. Both flavonols, acting as the major bioactive components (BCs) and anthocyanins, predominantly contributing to the color diversity of Epimedium flowers belong to different classes of flavonoids. It is well acknowledged that flavonoid biosynthetic pathway is predominantly regulated by R2R3-MYB transcription factor (TF) as well as bHLH TF and WD40 protein at the transcriptional level. MYB TFs specifically regulating anthocyanin or flavonol biosynthetic pathway have been already isolated and functionally characterized from E. sagittatum, but a R2R3-MYB TF involved in regulating both these two pathways has not been functionally characterized to date in Epimedium plants. In this study, we report the functional characterization of EsMYB9, a R2R3-MYB transcription factor previously isolated from E. sagittatum. The previous study indicated that EsMYB9 belongs to a small subfamily of R2R3-MYB TFs containing grape VvMYB5a and VvMYB5b TFs, which regulate flavonoid biosynthetic pathway. The present studies show that overexpression of EsMYB9 in tobacco leads to increased transcript levels of flavonoid pathway genes and increased contents of anthocyanins and flavonols. Yeast two-hybrid assay indicates that the C-terminal region of EsMYB9 contributes to the autoactivation activity, and EsMYB9 interacts with EsTT8 or AtTT8 bHLH regulator. Transient reporter assay shows that EsMYB9 slightly activates the expression of EsCHS (chalcone synthase) promoter in transiently transformed leaves of Nicotiana benthamiana, but the addition of AtTT8 or EsTT8 bHLH regulator strongly enhances the transcriptional activation of EsMYB9 against five promoters of the flavonoid pathway genes except EsFLS (flavonol synthase). In addition, co-transformation of EsMYB9 and EsTT8 in transiently transfected tobacco leaves strongly induces the expressions of flavonoid biosynthetic genes. The potential role of EsMYB9 in modulating the biosynthesis and accumulation of sucrose-induced anthocyanin and flavonol-derived BCs is also discussed. These findings suggest that EsMYB9 is a novel R2R3-MYB TF, which regulates the flavonoid biosynthetic pathway in Epimedium, but distinctly different with the anthocyanin or flavonol-specific MYB regulators identified previously in Epimedium plants.